If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = 3x + 4x Combine like terms: 3x + 4x = 7x 42 = 7x Solving 42 = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 42 + -7x = 7x + -7x Combine like terms: 7x + -7x = 0 42 + -7x = 0 Add '-42' to each side of the equation. 42 + -42 + -7x = 0 + -42 Combine like terms: 42 + -42 = 0 0 + -7x = 0 + -42 -7x = 0 + -42 Combine like terms: 0 + -42 = -42 -7x = -42 Divide each side by '-7'. x = 6 Simplifying x = 6
| (k/4)+6=-2 | | (2d-1)=15 | | 36-6e=6 | | 5x-2=1225 | | 5x-2=12.25 | | h=126t-16t^2 | | -6y*2-5y+2=0 | | 5x-(180-x)=300 | | 6x^2-23x+4=0 | | 2w^2-1w=36 | | 10+(x-2)=5-x+4 | | x-8+2=-7-1 | | 25-5d=-5 | | 0.5(x-2)=-x-2 | | -12=8+(f+2) | | 4a^2-4a+1=0 | | 9x^2-36z^4=0 | | 5(x+4)=8(x-2) | | 14=2(b-7) | | 5f=49 | | 4c-16=4 | | (s-2)14=63 | | -12-19=77 | | -161=23t | | 750*4x+17y= | | 3[5-3(4-y)]-5=5[(5y-4)+2]-26 | | 5m-3=2m+10 | | 3b-9=3 | | L^2-18L+72= | | x-4y-9=0 | | (t/6)-3=8 | | 7-2(5x-3)= |